SUZUKI METHOD AND THE “MOTHER TONGUE” - Decheva, Kalina (E-Journal VFU, 2024)
The Suzuki Method, no matter controversial or not, still attracts a considerable amount of followers. The following work is an attempt to clarify and interpret the Suzuki method from a perspective of the presence of language in it, to discover similarities in mastering a new language, as well as to analyze the influence of music education on the process of learning a foreign language.
Keywords: building block system; repetition; mother tongue; language acquisition; Suzuki Method